Career Adaptability and Student Subjective Wellbeing - Panjaitan, Yoko Jimmy; Pertiwi, Nisa Indah; Santika, Siti (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Research on subjective well-being is a currently trending and important topic to investigate because it will influence positive behaviors of students in their academic and other life aspects. Adaptability is a crucial skill for today's students to excel in preparing for their future careers. This research aims to examine the relationship between Career Adaptability and subjective well-being among students. However, there haven't been many studies that specifically focus on the student context. This study, the subjective well-being in will be centered around the variable of student’s subjective well-being, which directly observes subjective well-being in the context of students. Data collection methods involve using the Career Adapt-abilities Scale-Short form, developed by Maggiori and adapted into the Indonesian by previous researchers, and the Instrument of Student Subjective Well-Being measurement developed by Renshaw and Cook, which has also been translated in previous studies. The hypothesis of this research is that there is a positive relationship between career adaptability and the student’s subjective well-being. The research subjects consist of 301 students aged 18-29 years old in Indonesia. Data collection was done through online questionnaires. The Pearson correlation test using the JASP program yielded a value of p < 0.001 (< 0.05) with a correlation coefficient of 0.414. This indicates a significant positive relationship between career adaptability and the student’s subjective well-being, with an effective contribution of 41.4%. The higher student's career adaptability, the higher their subjective well-being, and higher student’s subjective well-being is associated with higher career adaptability.Penelitian mengenai kesejahteraan subjektif adalah tema yang menarik dan penting dikaji saat ini karena akan mempengaruhi perilaku positif mahasiswa dalam melakukan aktivitasnya, baik pada proses pembelajaran maupun aspek kehidupan lainnya. Kemampuan beradaptasi menjadi hal yang dibutuhkan bagi mahasiswa saat ini untuk dapat maksimal dalam mempersiapkan karir masa depan. Tujuan dari penelitian ini adalah mengetahui hubungan antara adaptasi karir dan kesejahteraan subjektif pada mahasiswa. Meskipun demikian, belum banyak penelitian yang mengkhususkan penelitian langsung kepada konteks pelajar atau mahasiswa. Kesejahteraan subjektif pada penelitian ini akan difokuskan menggunakan variabel student subjective well being yang akan langsung mengamati kesejahteraan subjektif dalam konteks mahasiswa. Metode pengumpulan data menggunakan alat ukur Career Adapt-abiities Scale-Short form yang dikembangkan oleh Maggiori dan telah diadaptasi ke bahasa Indonesia oleh penelti pada penelitian sebelumnya, serta Student Subjective Well Being Questionnaire yang disusun oleh Renshaw dan Cook dan telah dialihbahasakan pada penelitian sebelumya. Adapun hipotesis penelitian ini adalah adanya hubungan positif antara adaptasi karir dengan kesejahteraan subjektif mahasiswa. Subjek penelitian adalah 301 mahasiswa pada usia 18-29 tahun yang berada di Indonesia. Pengumpulan data dilakukan menggunakan kuisioner yang disebarkan secara online. Hasil uji korelasi pearson menggunkan program JASP memperoleh nilai p<0.001 (<0.05) dengan koefisien korelasi sebesar 0.414. Artinya terdapat hubungan positif yang signifikan antara adaptasi karir dan kesejahteraan subjektif mahasiswa dengan besarnya sumbangan efektif sebesar 41,4%. Hal ini berarti semakin tinggi adapatasi karir peserta didik akan cenderung menunjukkan semakin tinggi kesejahteraan subjektifnya, begitupla sebaliknya semakin tinggi kesejahteraan subjektif mahasiswa akan menunjukkan semakin tinggi adaptasi karinya.